Doege-Potter Syndrome: A Rare Paraneoplastic Syndrome of Solid Fibrous Tumors Reported in Indonesia - Peter Syarief; Evelyn Nathania; Ayunda Prameswari; Yumilia Hoo; Jahja Teguh Widjaja (Jurnal Respirasi, 2023)
Introduction: Solitary fibrous tumors (SFT) is a rare group of tumor. Even rarer, it is associated with Doege-Potter syndrome (DPS), which manifests as hypoglycemia due to paraneoplastic syndrome. From searching through national reports and articles, this was the first case of DPS in Indonesia. Case: A 60-year-old woman was admitted to the emergency department with dyspnea and unconscious. The patient's glucose level showed 21mg/dL. A solid mass on the patient's right lung was shown on the chest X-ray. A previous biopsy concluded that the patient had a solid fibrous tumor with a history of profound hypoglycemia. The patient underwent tumor resection and got a biopsy of the tumor. After resection, the patient showed no sign of hypoglycemia, and the blood glucose level was stable. We concluded that the patient had DPS, a paraneoplastic syndrome associated with the solid fibrous tumor. Conclusion: Performing an adequate examination and giving prompt treatments can increase the patient's quality of life, even though it is a rare disease and hard to diagnose. The patient's condition, evaluated from a clinical condition, chest X-ray, and blood glucose, was better than before getting radical resection.